Begonia dakrongensis (Begoniaceae), a new species from Dakrong Nature Reserve, Quang Tri province in Central Vietnam - Nguyen, Cuong Huu; Le, Anh Tuan; Ha, van Bac; Lin, Che Wei (Phytotaxa, 2024)
A new species of Begonia (Begoniaceae), B. dakrongensis, from Central Vietnam is described and illustrated. B. dakrongensis resembles B. abbreviata in its rhizomatous habit, short cymose-paniculate inflorescence with congested bracts, 4-tepaled staminate flowers, and 5-tepaled pistillate flowers. However, the new species markedly differs by having obtriangular-spathulate to oblong-obovate or widely obovate lamina (vs. ovate to broadly ovate), not oblique or nearly so (vs. oblique), widely obovate anthers (vs. narrowly obovate), and trigonous-globose ovary (vs. trigonous-ellipsoid).